Topological Fermi-arc surface state covered by floating electrons on a two-dimensional electride - Lim, Chan Young; Kim, Min Seok; Lim, Dong Cheol; Kim, Sunghun; Lee, Yeonghoon; Cha, Jaehoon; Lee, Gyubin; Song, Sang Yong; Thapa, Dinesh; Denlinger, Jonathan D.; Kim, Seong Gon; Kim, Sung Wng; et al. (Nature Communications, 2024)
Two-dimensional electrides can acquire topologically non-trivial phases due to intriguing interplay between the cationic atomic layers and anionic electron layers. However, experimental evidence of topological surface states has yet to be verified. Here, via angle-resolved photoemission spectroscopy (ARPES) and scanning tunnelling microscopy (STM), we probe the magnetic Weyl states of the ferromagnetic electride [Gd2C]2+·2e−. In particular, the presence of Weyl cones and Fermi-arc states is demonstrated through photon energy-dependent ARPES measurements, agreeing with theoretical band structure calculations. Notably, the STM measurements reveal that the Fermi-arc states exist underneath a floating quantum electron liquid on the top Gd layer, forming double-stacked surface states in a heterostructure. Our work thus not only unveils the non-trivial topology of the [Gd2C]2+·2e− electride but also realizes a surface heterostructure that can host phenomena distinct from the bulk.